2023
DOI: 10.1002/mnfr.202200841
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Mixed Probiotics Improves Photoaging by Modulating the Cecal Microbiome and MAPK Pathway in UVB‐Irradiated Hairless Mice

Abstract: Scope Continuous ultraviolet (UV) exposure causes skin photoaging, wrinkle formation, and skin barrier damage. In this study, the protective effect of mixed probiotics (MP) against photoaging in UVB‐irradiated Hs68 fibroblasts and SKH‐1 hairless mice is investigated. Methods and results The mice are irradiated with UVB for 8 weeks to induce photoaging, and MP (15 and 50 mg day−1) is orally administered once a day. Skin parameters are measured in the dorsal skin and wrinkle formation factors are analyzed in ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Oral prebiotics can either stimulate or restrain the proliferation of specific gut microbes, and it is now thought to regulate the growth of certain harmful skin microbes as well. Feeding mice with mixed probiotics has resulted in gut microbiome modulation and mitigation of UVB-caused skin aging by downregulating the MAPK pathway ( 84 ). Moreover, some studies ( 85 , 86 ) have reported that oral probiotics can alleviate skin inflammation in mice with skin conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Oral prebiotics can either stimulate or restrain the proliferation of specific gut microbes, and it is now thought to regulate the growth of certain harmful skin microbes as well. Feeding mice with mixed probiotics has resulted in gut microbiome modulation and mitigation of UVB-caused skin aging by downregulating the MAPK pathway ( 84 ). Moreover, some studies ( 85 , 86 ) have reported that oral probiotics can alleviate skin inflammation in mice with skin conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The result allows for regulating and maintaining skin health status by adjusting the balance of the gut microbiota. Studies have shown that altering the composition of the gut microbiota through fecal transplantation significantly improved the damaged state of skin photoaging [76]. This was mainly achieved by reducing the TNFR1/TNFR2-mediated MAPK pathway expression and altering intestinal amino acid metabolism [74].…”
Section: Gut Microbiota Balance and Fish By-product Proteinsmentioning
confidence: 99%